The Defensive Pessimism Among University Students: Psychological Strategy for Managing Academic Anxiety - Fatima Hawan Mohammed; RIAN VEBRIANTO (Jurnal Pendidikan (Teori dan Praktik), 2026)
This study examines defensive pessimism as a psychological strategy used by university students to regulate anxiety and prepare for academic challenges. Defensive pessimism refers to a cognitive strategy in which individuals set low expectations and mentally simulate potential negative outcomes to cope with anxiety and enhance performance. The study employed a quantitative descriptive design with a sample of 600 university students selected through stratified random sampling. A defensive pessimism scale consisting of 20 items was developed based on the theoretical framework of Norem and Cantor. The instrument demonstrated satisfactory psychometric properties with Cronbach’s alpha reliability of 0.89 and exploratory factor analysis confirming a single-factor structure. Data were analyzed using a one-sample t-test and two-way ANOVA. The results indicated that university students demonstrated significant levels of defensive pessimism. Furthermore, significant differences were found based on gender and academic specialization, where female students and students in humanities disciplines showed higher levels of defensive pessimism compared to their counterparts. These findings suggest that defensive pessimism functions as an adaptive cognitive strategy for managing academic pressure among students. The study contributes to the understanding of psychological coping strategies in higher education and provides implications for student counseling and academic support programs.